Improvement of adhesion strength of self-adhesive silicone rubber on thermoplastic substrates – Comparison of an atmospheric pressure plasma jet (APPJ) and a Pyrosil® flame. (April 2016) - Seitz, V.; Arzt, K.; Mahnel, S.; Rapp, C.; Schwaminger, S.; Hoffstetter, M.; Wintermantel, E.
Abstract: Polymeric hard/soft combinations consisting of a rigid, thermoplastic substrate and an elastomeric component offer many advantages for plastic parts in industry. Manufactured in one step by multi-component injection moulding, the strength of the thermoplastics can be combined with sealing, damping or haptic properties of an elastomer. Bonds of self-adhesive liquid silicone rubber (LSR) on high performance thermoplastics such as polyetheretherketone (PEEK) or polyphenylene sulphide (PPS) are especially interesting e.g. for medical applications due to their outstanding resistance properties. To ensure good adhesion between the two components, surface treatments from an atmospheric pressure plasma jet (APPJ) and a Pyrosil® flame are applied. Chemical changes on the thermoplastic surfaces are verified by water contact angle measurement (CA) and X-ray photoelectron spectroscopy (XPS). Plasma treatment causes a decline in water contact angle, indicating the formation of functional groups, especially –OH, on the surface. XPS measurements confirm the increase of oxygen on the surface. Thus, the number of functional groups on the thermoplastic surface is enlarged by plasma treatment, leading to stronger bonding to the organofunctional silanes of the self-adhesive silicone rubber. A thin layer of silanol groups is created by the Pyrosil® flame on the thermoplastic substrates, which could be verified by XPS. A hydrophilic behaviour of the coated surface is noticed. Both surface modification methods lead to enhanced adhesion properties of self-adhesive LSR on thermoplastic surfaces. This is confirmed by 90°- peel tests of the injection-moulded composites leading to an increase in peel force by the applied surface modification techniques.